(3GdQSGdI GdehSheI HCMO hSHYjf SDGd SFd HgG HYV GdeOYjf GdaSbI GdLgGd hGFeI GdLhQ hGdVdGds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG Cdge Hg ef TcQ BjGJg hfYeg MeO ef YQa bOQ ehGgHg hJhGJQ effg adg GdMeO GdOGFe hGdKfGA GdKGHJ s
(3BNQgG (B:s
(3hjJaVd Ydjg HfYeJg afgGjg Ydeg dGJYQa hHMGQ ahGFO dGJRa HLhOg HgG Ydi ChdjGFg hGdMeO ddg Ydi fYeg hGdBjg JeJ HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B72s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds